Sosialisasi Digital Marketing Pada Usaha Mikro Kecil Dan Menengah (Streetsteamgroup) - Diwangkara, Agustio; Soleh, Ahmad; Suwarni, Suwarni; Anggriani, Ida; Febrina, Tri (Jurnal Gotong Royong, 2024)
Digital marketing has become an important tool in supporting the growth of Micro, Small and Medium Enterprises (MSMEs) in the digital era. This research aims to examine the effectiveness of digital marketing socialization in MSMEs, particularly in the streetstemgroup sector. Streetstemgroups, which refer to groups of MSMEs operating in street areas or traditional markets, often face challenges in adopting digital technology. Through qualitative methods, this study analyzes the various socialization strategies implemented, including training, workshops, and the use of social media platforms. The results show that digital understanding and skills acquired through socialization have a significant impact in increasing the visibility and sales of streetstemgroup MSMEs. However, the successful implementation of digital marketing is also influenced by internal factors such as the commitment of entrepreneurs and external support from the government and community. This research suggests the need for continuous collaboration between the government, private sector and community to maximize the potential of digital marketing in empowering streetstemgroup MSMEs.